2021
DOI: 10.3991/ijet.v16i06.13535
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality and BIM Methodology as Teaching- Learning Improvement Tools for Sanitary Engineering Courses

Abstract: Virtual Reality (VR) is the term often used to describe a 3D environment where objects and images of the real world are simulated through technology. In Architecture or Civil Engineering, the design process with 2D planes could lead to error due to misinterpretation in the visualisation of elements. The civil engineering programme of a University mandates teaching of the BIM methodology in all courses, allowing the students to learn about the organisation and optimisation of projects from design to constructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…This can be explained, due to the fact that many teachers have used various teaching strategies, such as simulation software and tools used for various calculations; It can be pointed out that the more visual the learning is made, the greater the volume of content that will be processed and incorporated in the form of knowledge. In this way, better retention is also achieved and an increase in the student's security in relation to the solidity of the knowledge that he is acquiring [14].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…This can be explained, due to the fact that many teachers have used various teaching strategies, such as simulation software and tools used for various calculations; It can be pointed out that the more visual the learning is made, the greater the volume of content that will be processed and incorporated in the form of knowledge. In this way, better retention is also achieved and an increase in the student's security in relation to the solidity of the knowledge that he is acquiring [14].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Fernanda [7] proposed that the construction management course should facilitate students to master the BIM applications in different project phases and gain the ability of construction management optimization on this basis. Espinoza et al [8] studied the applications of virtual reality and BIM in sanitary engineering course teaching, and believed that their study results can help in the implementation of the pipeline engineering course in the civil engineering specialty. Brok-bals [9] suggested that institutions of higher learning should strengthen the teaching exploration into interdisciplinary BIM projects.…”
Section: State Of the Artmentioning
confidence: 99%
“…BIM makes it possible to consider the entire life cycle of a project, from design to use [14]. Finally, BIM supported by virtual reality in plumbing helps students visualize plumbing fixtures and learn integrated design in an innovative way [15].…”
Section: Scenarios Of Building Information Modelling-based Design Edu...mentioning
confidence: 99%